Sharpening Critical Reasoning: The Application of Problem-Based Learning in Writing Explanatory Texts in Elementary Schools - Royani, Siti; Widayati, Mukti; Nurnaningsih, Nurnaningsih (Universitas Cokroaminoto Palopo, 2025)
The aims of this research lies in discussions related to the application of the Problem Based Learning (PBL) model in learning to write explanatory texts; (2) Describe aspects of critical reasoning based on the 4C category (Critical Thinking, Creativity, Collaboration, Communication) in learning to write explanatory texts by applying the PBL model, and (3) Describe the implications of applying the PBL model in writing explanatory texts as a reinforcement of critical reasoning dimensions based on category 4C for class VI students at SD Negeri Sraten 02 Gatak Sukoharjo for the 2024/2025 academic year. The data used are the results of observations, interviews and documentation related to a series of student activities in learning to write explanatory texts using the PBL model; critical reasoning aspects mastered by students. Data sources were obtained from teachers and students of class VI SD Negeri Sraten 02 Gatak Sukoharjo. Data was collected using observation, interviews and documentation. Data validity uses triangulation of sources, methods and theories. Data was analyzed using interactive analysis starting from data collection, data reduction, data presentation, and drawing conclusions. The research results showed that the implementation of learning to write explanatory texts using the PBL model was carried out in the stages of problem orientation; learning organization towards problems; investigation; development of work results, and continuous evaluation. The aspects of critical reasoning that students master are creative thinking, creativity, collaboration and communication which are based on active interaction and student independence in learning.